LAB RATS : How Silicon Valley Made Work Miserable For The Rest Of Us - Lyons, Daniel, 1960-
Examines how the ideas of Silicon Valley and its new oligarchs have changed work culture, making employees subject to constant change, dehumanizing technologies, and even health risks, and discusses how to restore the social contract between employers